Perceived Usefulness, Ease of Use, and Intention to Use Gregg Shorthand for On-the-Job Training: Evidence from 4th-Year Office Administration Students - Higan, Cecille C.; Cortez, Katrina Cassandra G.; Molina, Mary Joy B.; Guballo, Jayvie O. (Journal of Management Studies and Development, 2025)
The current study examines the influence of perceived usefulness and perceived ease of use on the intention of fourth-year Bachelor of Science in Office Administration students to utilize Gregg Shorthand during their On-the-Job Training (OJT). With the evolution of technology and its impact on administrative tasks, the practical relevance of shorthand remains uncertain in modern training settings. Grounded in the Technology Acceptance Model, the study aimed to assess how students perceive the usefulness and ease of use of Gregg Shorthand and whether these perceptions influence their intention to use it. A quantitative approach was utilized, surveyed 178 students from Rizal Technological University with a structured questionnaire. Results from simple linear regression analysis indicated that perceived usefulness (β = 0.834, p = 0.001) and perceived ease of use (β = 0.879, p = 0.001) strongly and positively influence intention to use Gregg shorthand during OJT. The empirical findings suggest students are more inclined to use Gregg Shorthand when they perceive it as beneficial and easy to use. These conclusions indicate that shorthand could still be valuable in administrative training if taught more practically and relevantly. The study emphasizes the need to focus on curriculum alignment with practical applications and recommends enhancement of the syllabus pertinent to shorthand instructions, especially in fields demanding rapid accuracy. Furthermore, the study recommends more exploration into field-specific approaches concerning the needs of students and instructional design to enhance performance and engagement with Gregg Shorthand.